Between duty and desire : pre-nuptial pregnancy and unmarried motherhood in Anglican Cape Town during the first half of the twentieth century - Richardson, Laura Jane (Stellenbosch : Stellenbosch University, 2020)
Thesis (MPhil)--Stellenbosch University, 2020.